2016
DOI: 10.1371/journal.pone.0161308
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of TaRca2-α Gene Associated with Net Photosynthesis Rate, Biomass and Grain Yield in Bread Wheat (Triticum aestivum L.) under Field Conditions

Abstract: Improvement in activation of Rubisco by Rubisco activase can potentially enhance CO2 assimilation and photosynthetic efficiency in plants. The three homoeologous copies of TaRca2-α were identified on chromosomes 4AL, 4BS and 4DS (TaRca2-α-4AL, TaRca2-α-4BS, and TaRca2-α-4DS) in bread wheat. Expression patterns of the three copies at heading (Z55), anthesis (Z67) and grain-filling (Z73) stages were investigated through qRT-PCR analyses in a panel of 59 bread wheat genotypes and their effects on net photosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This underlying unknown molecular mechanism for microbe-plant cell signaling is yet to be explored. Similarly, the expression of TaGlk1 involved in the maintenance of photosynthetic apparatus, TaPORA related to chlorophyll biosynthesis ( Rauf et al, 2013a ), TaRcaB gene for fixation of CO 2 ( Saeed et al, 2016 ), TaFTSH2 gene for photosystem II repair, and TaTIF5A-1 gene for protein biosynthesis was downregulated in waterlogging stressed wheat plants, but differentially induced in MAP1-inoculated, waterlogged stressed plants compared to non-inoculated waterlogged wheat. Heat shock proteins (HSPs) are major “molecular chaperones” that act as protein folding catalysts and may enhance tolerance against stresses.…”
Section: Discussionmentioning
confidence: 99%
“…This underlying unknown molecular mechanism for microbe-plant cell signaling is yet to be explored. Similarly, the expression of TaGlk1 involved in the maintenance of photosynthetic apparatus, TaPORA related to chlorophyll biosynthesis ( Rauf et al, 2013a ), TaRcaB gene for fixation of CO 2 ( Saeed et al, 2016 ), TaFTSH2 gene for photosystem II repair, and TaTIF5A-1 gene for protein biosynthesis was downregulated in waterlogging stressed wheat plants, but differentially induced in MAP1-inoculated, waterlogged stressed plants compared to non-inoculated waterlogged wheat. Heat shock proteins (HSPs) are major “molecular chaperones” that act as protein folding catalysts and may enhance tolerance against stresses.…”
Section: Discussionmentioning
confidence: 99%
“…The relative expression and protein abundance of these three isoforms in relation to one another may be an important factor in wheat heat stress tolerance. Higher amounts of TaRca2-a expression under nonstressed physiological conditions have been reported to be linked to increased photosynthesis, biomass, and yield in wheat (Saeed et al, 2016). Furthermore, the protein profile of wheat Rca determined by westernblot analysis shows that there are two bands corresponding to an aand a b-isoform and abundance of a third band in close proximity to the position of the original b-isoform when wheat is exposed to heat stress (Law and Crafts-Brandner, 2001;Ristic et al, 2009).…”
mentioning
confidence: 99%
“…61 Rubisco activase (RCA) regulates the activity of Rubisco, and the expression of RCA in bread wheat contributes substantially to the net photosynthesis rate and crop yield. 62 Therefore, the up-accumulation of RAF1 and RCA may account for the increased level of RBCS1B and hence promote CO 2 fixation in Bndcl1. Previous research revealed that adenosine monophosphate kinase 2 (AMK2) plays key roles in reversible formation of ADP in the plastid stroma and its expression is positively correlated with the expression of genes required for photosynthesis.…”
Section: ■ Discussionmentioning
confidence: 99%